Exposing emotional labour experienced by nursing students during their clinical learning experience: A Malawian perspective - Gladys Msiska; Pam Smith; Tonks Fawcett (Elsevier, 2014)
Background: Clinical nursing education is a fundamental component in the pre-registration nursing curriculum and literature reflects its challenges. Aim: The study investigated the clinical learning experience of undergraduate nursing students in Malawi to explore their perceptions of the experience. Design: This was a hermeneutic phenomenological study. Setting: The study took place at a University Nursing College in Malawi. Participants: Participants for the study were purposively selected from among third and fourth year undergraduate nursing students. The sample consisted of 30 participants and their participation was voluntary. Methods: Conversational interviews were conducted to obtain participants' accounts of their experience and a framework developed by modifying Colaizzi's procedural steps guided the phenomenological analysis. In a hermeneutic phenomenological study, interpretation is critical to the process of understanding the phenomenon being investigated. The findings have been interpreted from a perspective of emotions, utilising emotional labour (Hochschild, 1983) as a conceptual framework which guided the interpretive phase. Results: The study findings reveal that the clinical learning experience is suffused with emotions and students appear to engage in management of emotions, which is commonly understood as emotional labour. Emotional labour is evident in students' narrative accounts about their caring encounters, death and dying and caring-learning relationships as they interact with clinical nurses and lecturers during their clinical learning experience. Conclusion: Effective clinical teaching and learning demands the emotional commitment of lecturers. The understanding of emotional labour in all its manifestations will help in the creation of caring clinical learning environments for student nurses in Malawi.